Design of lubricating grease formulations using recycled polypropylene from postconsumer films as thickener agent. Issue 2 (24th May 2012) - Martín‐Alfonso, J. E.; Valencia, C.; Arteaga, J. F.; Díaz, M. J.; Franco, J. M.
Abstract This work deals with the design of lubricating greases formulations based on blends of mineral oil and recycled polypropylene from postconsumer waste, coming from films with inks. In particular, the influence of polymer concentration on the rheological, mechanical, and thermal properties of recycled polymer/oil blends was characterized. From the experimental results obtained, it can be deduced that the evolution of recycled polymer/mineral oil formulations on linear viscoelasticity functions with frequency is quite similar to that found for traditional lithium greases. It is observed that these blends form systems with enhanced "plateau" modulus, G<alternatives> No</alternatives>, with respect to industrial standard lubricating greases, which could be represent an important advantage, from an economic and environmental point of view. However, the influence of temperature on linear viscoelasticity functions is more pronounced than that found for traditional greases. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013